(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This study analyzes the ethnographic types of traditional Uzbek embroidered headdresses, focusing on their historical, cultural, and regional significance. Special attention is given to women’s peshonaband and men’s salla from Bukhara, highlighting embroidery techniques such as zardozi. The research demonstrates how these headdresses function as cultural identifiers and artistic heritage. Contemporary relevance and preservation efforts are also discussed to underscore their importance in modern Uzbek identity.